The Effects of Childhood Sexual Abuse: The Role of Anxiety and Alcohol Use among Haitian Women Living with HIV. Issue 7 (2nd October 2020) - Villalba, Karina; Attonito, Jennifer; Jean-Gilles, Michele; Rosenberg, Rhonda; Sanchez, Mariana; Devieux, Jessy
ABSTRACT: Childhood abuse has been linked to problematic drinking in adulthood. It is also documented that people living with HIV have higher rates of alcohol use than the general population. In Haiti, a total of 25% of women living with HIV have experienced childhood sexual abuse (CSA), which puts them at an increased risk for alcohol abuse. CSA has also been associated with anxiety disorders in adulthood. Therefore, it is critical to understand the relationship between CSA, anxiety, and alcohol use among women living with HIV. A total of 244 women living with HIV participated in this study, with 35% reporting CSA. Alcohol abuse was measured with the AUDIT, anxiety with the State-Trait Anxiety Inventory test, and sexual abuse with the Childhood Trauma Questionnaire. Compared to participants who did not experience childhood sexual abuse, participants who experienced childhood sexual abuse reported greater levels of alcohol use [(17.0, SD = 9.1) (11.9, SD = 8.6) p =.001] and anxiety [(55.8, SD = 9.8) (48.9 SD = 8.3) p =.001] respectively. The indirect effect of anxiety on the association between CSA and alcohol use was significant [(ß =.19 p =.05) 95% bootstrap CI.019 –.13] Thus, women who reported being sexually abused as children reported anxiety, which in turn, was associated with an increased risk for alcohol abuse. Results demonstrate that alcohol may be used as a negative coping mechanism to alleviate anxiety symptoms triggered by CSA. These findings elucidate the need for further research examining the impact that sexual trauma has on mental health.